Socio System of Kirat of Nepal - An Empirical Mini-Study with special reference to Kirat-Limbu - Siddiqui, Salahuddin Akhtar (2016)
This study is focused on socio-system of Kirat people of Nepal. To study the socio-system of whole Kirat people of Nepal is very much vague content area by nature. So, introduction, history and demography of Kirat people of Nepal is comprised wholly, then, the study is narrowed down to only Kirat-Limbu. Focusing to Kirat-Limbu, this study deals the family structure, family system along with social concept and practice including birth to death rite and rituals, food habits, provisions of social system in Mundhum. This study also tries to indicate contrastive areas between social system of Mundhum and family laws of Nepal, drawing the conclusion.